Analysis of players` stroke performance relevance in tennis matches - Gao, H.; Liu, W.; Zhang, H. (International Journal of Performance Analysis in Sport, 2024)
In this study, we applied the stroke performance relevance (SPR) method to analyse the performance of players in 53 elite men`s singles matches at the 2018 and 2019 Australian Open, Roland Garros, and Wimbledon championships. The SPR method assigns a distinct contribution value to each stroke, considering the stroke`s outcome and timing. The investigation scrutinised every stroke, analysing stroke technique, placement, and game action across three court surfaces to understand their impact on match outcomes. The results revealed that 1) serve technique is crucial in high-level men`s singles matches, especially on hard court and grass, while groundstrokes significantly influence match outcomes. Forehand groundstrokes, with notably higher SPR values than backhand groundstrokes, are more beneficial for winning players. 2) Court surfaces minimally impact stroke placements; deeper and closer-to-the-sideline shots yield better scores on all courts. 3) Neutral actions (both players use offensive techniques to strike the ball) show significant differentiation in match outcomes. For both players who won match and players who lost the match, negative SPR values for return and defence across different courts indicate a negative impact on match outcomes. 4) SPR is a new method to help coaches and players quantify stroke performance in matches.